Essentials of dance movement psychotherapy international perspectives on theory, research, and practice - Payne, Helen 1951- (London Routledge, Taylor & Francis Group, 2017)
Essentials of Dance Movement Psychotherapy contributes to the global interest in embodiment approaches to psychotherapy and to the field of dance movement psychotherapy specifically. It includes recent research, innovative theories and case studies of practice providing an inclusive overview of this ever growing field. As well as original UK contributions, offerings from other nations are incorporated, making it more accessible to the dance movement psychotherapy community of practice worldwide. Helen Payne brings together well-known, experienced global experts along with rising stars from the field to offer the reader a valuable insight into the theory, research and practice of dance movement psychotherapy. The contributions reflect the breadth of developing approaches, covering subjects including: combining dance movement psychotherapy with music therapy; trauma and dance movement psychotherapy; the neuroscience of dance movement psychotherapy; the use of touch in dance movement psychotherapy; dance movement psychotherapy and autism; relational dance movement psychotherapy. It will be a treasured source for anyone wishing to learn more about the psychotherapeutic use of creative movement and dance. It will be of great value to students and practitioners in the arts therapies, psychotherapy, counselling and other health and social care professions.
Introduction: Experiencing inter-corporality and professional learning -- Part I: Theory -- Relational dance movement psychotherapy: A new old idea -- Dynamic equilibrium: Engaging neurophysiological intelligences through dance/movement therapy -- Conscious movement sequencing: The core of the dance/movement therapy experience -- A phase model of growth in dance therapy -- Part II Research -- Gestalt and dance movement psychotherapy: Moving towards integration through practice and research in adults with eating disorders -- The use of touch in dance/movement therapy: A phenomenological study -- A dance informed contribution to nonverbal interpersonal relating in autism spectrum disorders -- Movement-based supervision for Korean arts therapies students -- Part III Practice -- Reliable change in outcomes from The BodyMind Approach with people who have medically unexplained symptoms/somatic symptom disorder in primary health care -- Overcoming trauma: When verbal language is not enough -- I am here with you: Dance movement therapy and music therapy as a marriage of empathy in the special school setting -- Holding and adolescent angst: Significant moments within a dance movement psychotherapy group in a mainstream secondary school -- The recovery journey: The place and value of dance movement psychotherapy with clients with alcohol or substance misuse -- Appendix
Includes bibliographical references and index.
Keywords: Dance therapy; Movement therapy